Biotransformation of (R)-(+)-lLimonene by the psychrotrophic fungus Mortierella minutissima in H2O2-oxygenated culture - Trytek, Mariusz (Array, 2009)
Summary: The aim of the present work is to investigate an integration of a microbial reaction system for the oxidation of limonene using a psychrotrophic strain with an unconventional oxygenation of the culture. The alternative method for increasing the dissolved oxygen concentration in culture media for biotransformation of R-(+)-limonene by Mortierella minutissima 01 is based on catalase-mediated decomposition of hydrogen peroxide (H2O2) into oxygen and water. Automated addition of H2O2 into the bioreactor made it possible to keep the dissolved oxygen concentration constant over a range from 5 to 100 % (±2 %). Perillyl alcohol and perillyl aldehyde were the main products of the limonene biotransformation. The amounts of perillyl alcohol produced during H2O2-oxygenated culture of M. minutissima 01 were over 2-fold higher in comparison with classical, stirred aeration. Some factors affecting the biotransformation yield were also investigated. The addition of 0.3 % methanol enhanced 1.4-fold the perillyl alcohol production by M. minutissima 01. A maximum yield of this product (258.1 mg/L) was observed between 2 and 3 days of cultivation in a medium containing 0.5 % substrate at 15 °C, pH=6.0. The bioconversion activity increased over 3.6-fold after optimization of some biotransformation conditions